(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study explores the recent use of Project Portfolio Management (PPM) methodologies in the public service. A literature review was conducted to identify the characteristics of public organizations that initiate the adoption of the PPM, the methodologies and practices that have been used and other relevant aspects of the topic.